Analysis of Electrical Energy Contained in Vegetables - Annisa Tri Banoeari; Tariza Humaira Tembusai; Riris Siahaan (Universitas Negeri Medan, 2021)
This study aims to determine the source of electrical energy in potatoes and lime. The method used is based on the principle that the salt content in potatoes is a solution, where salt is the solute and water is the solvent, so the ions can move freely. The movement of the ions in the potato can conduct electricity. For the contained acid lime affects the hardness of the composite, which affects the matrix and filler bonds. oxalic acid, which is in lime juice, is a type of electrolyte solution. In a voltaic cell, the electrolyte solution can function to deliver ions from the anode to the cathode so that it can produce electrical energy. Electrical energy is energy that is very important in life. Electrical energy is a basic human need so that potatoes and lime can be used as an alternative source of electrical energy.